Between bits and dollars: challenges for financing contemporary photojournalism - da Silva Júnior, José Afonso; Peixoto, João Guilherme de Melo (Brazilian journalism research, 2013)
Photojournalism is currently undergoing the largest set of changes to its productive chain since its incorporation to digital and network processes. These changes affect the means of production, edition and circulation of content and create new challenges and purposes for the activity. In this study, we have found that going beyond ontological issues, aspects related to economics and funding of photojournalism are also changing. As a method of analysis, we compare the possibilities on this framework to the traditional model used by newspapers and magazines, at a time we can call pre-convergent photojournalism. Additionally, we aim to point out the main alternatives to these trends.